User-Generated Contents, Purchase Intention, and the Mediating Role of Attitude- Exploring the Context of Developing Nations - Dahliana; Jannat, Rabeya; Abir, Tanvir; Zarin, Nowshin; Francis Peris, Sandy (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
This paper explored the impact of User-generated content (UGC) on consumer purchase intention and the mediating role of attitude towards UGC. By analyzing factors like brand engagement, perceived credibility, perceived usefulness, and information quality, this research aims to shed light on the connections between these variables. Quantitative data was collected from 208 individuals using an online survey. SEM-PLS was used for data analysis. Findings revealed that the identified components of UGC significantly influence attitude, which, in turn, shapes purchase intentions. This research contributes to the understanding of how UGC can be harnessed by marketers to communicate value to customers and enhance purchase intention. It also highlights the indirect impact of UGC on purchase intention, mediated by the attitude toward UGC. Apart from enriching the existing literature, particularly from a developing nation’s perspective; the findings provide insights for mobile phone marketers in Bangladesh to benefit from the potential of authentic customer experiences to drive purchase intentions in a dynamic digital landscape.